2017
DOI: 10.22159/ajpcr.2017.v10i10.19302
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidine Incorporated Schiff Base of Isoniazid With Their Synthesis, Characterization and in Vitro Biological Evaluation

Abstract: Objective: Versatile biological activities of nitrogen containing heterocycles in medicinal chemistry, mainly pyrimidine and pyridine ring based heterocyclic moieties are very important. Pharmaceutical important of pyrimidine and isoniazid moiety prompted us to synthesize isoniazid clubbed pyrimidine derivatives and evaluated for antimicrobial and antituberculosis activity. Results: Majority of the compounds exhibited good antibacterial, antifungal, and antituberculosis activity. All titled compounds were char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Fifth and 6 th position fused with other heterocyclic ring and o, m, p substituted with aryl ring. This substitution leads to anticancer antiviral, antibacterial, vasodilation, and treatment of UTI [5,[7][8][9][10][11].…”
Section: Position Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth and 6 th position fused with other heterocyclic ring and o, m, p substituted with aryl ring. This substitution leads to anticancer antiviral, antibacterial, vasodilation, and treatment of UTI [5,[7][8][9][10][11].…”
Section: Position Dmentioning
confidence: 99%
“…The wide range of biological activity and versatile synthetic applicability of these heterocyclic compounds will help the medicinal chemists to plan, organize and implement new approaches toward discovery of novel drugs. Thus, pyrimidine compounds received much attention from medicinal as well as synthetic organic chemists [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis. The preparations of m 0 CNpCH 3 [Sm6p] (Merchant et al, 1965) and m 0 BrpCH 3 [Dm6p] have previously been reported (Budakoti et al, 2008;Ellsworth et al, 2008;Rangarajan et al, 2016;Soni & Patel, 2017;Zhang et al, 2017). Ethanol (1.5 mL, 95%) and a magnetic stir bar were added to two separate Biotage microwave vials (2-5 mL); one contained 4-methylbenzaldehyde (3 mmol) and the other contained 3 0 -acetophenone (3 mmol).…”
Section: Synthesis and Crystallizationmentioning
confidence: 99%
“…Griseofulvin and nystatin used as a standard antifungal drug. Majority of the compounds exhibited good antibacterial, antifungal, and antituberculosis activity [67].…”
Section: Mohanambal Et Almentioning
confidence: 99%